Habilidades sociais educativas de professores de pré-escolares com desenvolvimento típico, problemas de comportamento e deficiência - Guimarães, Cristiane de Azevedo (Universidade Federal de São Carlos, 2019)
Each stage of development, added to the specific characteristics of the students, may require a different management by the teacher in terms of educative social skills. Thus, this study aimed to: characterize the educative social skills of pre-school teachers with typical development, behavior problems and disabilities; characterize the repertoire of social skills and behavior problems of children, in the teacher's view; compare social skills and behavior problems in children with typical development, behavior and disability problems; compare social skills and behavior problems in children related to gender and type of school; relate teachers' social skills to behavior problems and children’s social skills. Thirty-two teachers from the common class of Early Childhood Education participated in the study; all of them had at least one Special Education Child in Development (PAEE) student registered in their current classroom. The teachers answered individually to the following instruments: 1) Preschool Kindergarten Behavior Scales (PKBS) to evaluate the repertoire of social skills and behavior problems of three preschool students (a special or late education child in development, a child with typical development, and a child with behavior problems); 2) Inventory of Educative Social Skills that describes behaviors presented by teachers related to the students; 3) Educative Social Skills Questionnaire (QHSE) of the preschool teacher in daily situations at school. The data collected by the instruments was analyzed according to previous instructions of the authors. Pearson's correlation test was used to link the data. T-test and the Anova were used to compare social skills and behavior problems of children. The results indicated that in the self-assessment the teachers have a high repertoire of Educative Social Skills. It was noticeable that teachers self-assessed more positively in the IHSE-Pr in the two following topics: give instruction about activity and organize physical environment. In the QHSE instrument, the teachers presented more difficulties in the topics: establish interactive context and establish limits and discipline. There were statistically significant differences in behavior problems and social skills among students with typical development, behavior problems and disabilities, when the comparison is related to gender. In the comparison of social skills and behavior problems between the groups, it was observed that, in general, children with typical development presented a repertoire of broader and refined social skills, in addition to lower rates of behavior problems. On the other hand, children with behavioral and disability problems presented similar average values in most of the social skills factors. No significant correlation was found between the educative social skills repertoire of the teachers and social skills and behavioral problems of the children. However, some factors related to the educative social skills of the teachers had a significant positive correlation with sociodemographic variables, such as teacher age and professional experience. Considering these results and the goals of the National Education Plan, it is important to promote public policies aimed at training the teacher of Early Childhood Education in educative social skills to favor the overall development of their students regardless of their characteristics.
Educative social skills of pre-school teachers with typical development, behavior problems and disabilities
Keywords: Educação Especial; Habilidades sociais educativas; Educação Infantil; Professor; Desenvolvimento típico; Problemas de comportamento; Deficiência; Special Education; Educative social skills; Child education; Teacher; Typical development; Behavior problems; Deficiency; CIENCIAS HUMANAS::EDUCACAO